Dakwah Dan Demokrasi : Analisis Tentang Kontribusi Dakwah Dalam Penegakan Demokrasi - Choiriyah Choiriyah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Preaching is the work being done to realize the teachings in every dimension of human life. Democracy as a form of government that is run by the seat of the people as sovereign, will require people who understand his role. There are three roles in this respect that the people choose their leaders, to exercise control over government policies and determine the government's goals to be realized. Therefore, the propagation in this case need to contribute in an effort to educate people to be able to play those roles. Contribution in this mission is to provide information about the proper criteria for elected leaders, provide information about policies such as what needs to be done by government and the purpose or direction to be taken in bringing prosperity for his people. Thus the people in this mission as well as the practitioner can provide control of any government policy or perform the function of doing good and avoiding evil amr.